Key Features of Russian and International Accounting of Entities in State Sector - L. B. Trofimova (Вестник Российского экономического университета имени Г. В. Плеханова)
In this research the author found the necessity to work out finance accounting of the public sector that takes into account key specific features used by state entities. To insert corrections in recommended by international standards IPSAS patterns of the form of accounting the author studies basic factors affecting the structure of report on finance standing and report on finance results of work of entities in state sector. On the basis of analyzing features of economic resources shown in conceptual foundations of finance accounting of general use of organizations in the public sector proposals were elaborated aimed at upgrading the pattern of report on finance standing of entities of state sector put forward in the international standard IPSAS 1 ‘Presenting Finance Accounting’. As a key characteristic of keeping budget accounting the author used the classification of work in state institutions that is connected with creation of the service potential and the work that provides future economic benefits for the entity. During the research the author found certain discrepancies and shortcomings in standards of the state sector. Practical importance of the research is connected with elaboration of grounded proposals on further improvement and development of the federal standard of accounting in the state sector in the Russian Federation